Implementasi Perjenjangan Buku dalam Meningkatkan Kemampuan Literasi Peserta Didik di SDN Sanghiang - Amanda, Dhea; Isrok’atun, Isrok’atun; Julia, Julia (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Book leveling is a combination of books and target readers. The aim of this research is to determine the implementation of book grading in elementary schools as an effort to increase students' literacy skills. The research method used was qualitative research with research subjects being students and the principal of SDN Sanghiang. Data collection techniques are interviews and documentation. The research results show that the implementation of book tiering is in accordance with SK NO.030_P_2022. The leveling process for this book is divided into five levels, namely level A (early readers), level B (early readers), level C (senior readers), level D (advanced readers), and level E (advanced readers). The results of the implementation of book leveling show an increase in understanding of the contents of the books read by students so that book leveling is an effective effort in increasing students' literacy skills.